2021
DOI: 10.2337/db20-1157
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Mitochondrial Glycerol 3-Phosphate Dehydrogenase Exacerbates Podocyte Injury and the Progression of Diabetic Kidney Disease

Abstract: Mitochondrial function is essential for bioenergetics, metabolism, and signaling and is compromised in diseases such as proteinuric kidney diseases, contributing to the global burden of kidney failure, cardiovascular morbidity, and death. The key cell type that prevents proteinuria is the terminally differentiated glomerular podocyte. In this study, we characterized the importance of mitochondrial glycerol 3-phosphate dehydrogenase (mGPDH), located on the inner mitochondrial membrane, in regulating podocyte fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Studies have shown that podocyte injury plays a key role in the pathogenesis of DN [ 9 , 10 ]. The number and density of podocytes in the early stage of DN have begun to decrease and worsen with the aggravation of the disease [ 11 ]. The density and total number of podocytes are reduced by apoptosis and shedding due to injury, and the residual podocyte widens and fuses, resulting in compensatory hypertrophy, leading to glomerular sclerosis and destruction of the glomerular filtration barrier [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that podocyte injury plays a key role in the pathogenesis of DN [ 9 , 10 ]. The number and density of podocytes in the early stage of DN have begun to decrease and worsen with the aggravation of the disease [ 11 ]. The density and total number of podocytes are reduced by apoptosis and shedding due to injury, and the residual podocyte widens and fuses, resulting in compensatory hypertrophy, leading to glomerular sclerosis and destruction of the glomerular filtration barrier [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A secreted glycoprotein, progranulin, can activate SIRT1/PGC-1α/FOXO1 signaling in podocytes exposed to HG, which protected against podocyte injury in mice with DN ( 62 ). Recent finding emphasized the importance of mitochondrial glycerol 3-phosphate dehydrogenase in inducing mitochondrial biogenesis in podocytes, which protected the cells against hyperglycemia-induced impairment of mitochondrial bioenergetics and increased ROS production ( 63 ).…”
Section: Mitochondrial Biogenesis In Diabetesmentioning
confidence: 99%
“…Accumulation of mtROS has been shown in various CKD, including DN and FSGS, and enhanced mtROS production recently confirmed in diabetic db/db mice by real-time mitochondrial redox assessment [ 90 ]. Moreover, podocyte-specific overexpression of the antioxidant metallothionein ameliorates experimental DN [ 91 ], while podocyte-restricted deletion of mitochondrial glycerol 3-phosphate dehydrogenase exacerbates mitochondrial oxidative stress, podocyte loss, and proteinuria in animal models of both DN and FSGS [ 92 ]. However, most of the studies did not identify the glomerular cell type in which mtROS exert their deleterious effect [ 93–95 ].…”
Section: Mechanisms Of Podocyte Injurymentioning
confidence: 99%